TINGKAT PENGETAHUAN DAN STATUS KARIES WARGA MUHAMMADIYAH KARANGTENGAH, IMOGIRI, BANTUL, YOGYAKARTA - Dyah Triswari; Dwi Aji Nugroho; Nia Wijayanti; Dheya Shafarah Salwa; Aisyah Salsabila (Universitas Muhammadiyah Mataram, 2023)
Dental and oral health knowledge is still lacking so there are still many dental and oral diseases that are suffered by the community. Lack of knowledge about this causes poor oral hygiene status and caries status. Educational activities about dental and oral health as well as simple dental health care are beneficial for increasing dental and oral health care and awareness in the community. A social service is a form of community service that aims to increase knowledge of the importance of dental and oral health to residents. This activity uses counselling techniques, and dental health care services, and ends with DHE (Dental Health Education). DHE is to provide an understanding that contains directions on procedures for maintaining healthy teeth and mouth. Counselling was carried out at the Nurul Islam Mosque in Karangtengah Pimpinan Ranting Muhammadiyah (PRM) starting with a pre-test and post-test on knowledge of systemic diseases and their relation to oral health. The results showed that there was an amplification of the residents' knowledge, namely an increase of 7.7% as seen from the results of the post-test. The dental and mouth examination was attended by 97 members of Muhammadiyah Karangtengah consisting of 18 children, 40 adults and 39 elderly. Dental examination and treatment followed by DHE as a form of education given after treatment.